Effective chemical control of fruit flies (Diptera: Tephritidae) pests in mango orchards in northern Côte-d’Ivoire - N'Depo, O. Robert; Hala, N.; N'Da Adopo, A.; Coulibaly, F.; Kouassi, P.K.; Vayssières, Jean-François; Meyer, M. de (African Journals Online, 2015)
Fruit flies are major pest in West Africa. In Côte-d’Ivoire, they caused heavy losses. Thus, preventive measures are taken to reduce their damage. The objective was to evaluate the effectiveness of Success Appat® and Proteus 170 O-TEQ against fruit. Traps baited with sexual attractants were set in mango orchards and their contents were collected each week. Bait and insecticide were renewed each month. Three orchards were treated with Success Appat® and three with Proteus 170 O-TEQ, respectively and their untreated orchards were selected. Mangoes were collected in treated and untreated orchards to assess the attack and infestation rates of orchards. Eight species of fruit flies were recorded. Bactrocera invadens was highly captured in different orchards. Orchards treated with Success Appat® have a lower rates of attack (11.7 ± 3.52%) and infection (02.32 ± 1.6 pupae/ kg.f) than the untreated orchards, (41.05 ± 7.6%) and (34.4 ± 8.18 pupae/ kg.f), respectively. Equally, orchards treated with Proteus 170 O-TEQ showed lower rates of attack (13.59 ± 5.38%) and infection (05.86 ± 4.08 pupae/ kg.f) than untreated (47.37 ± 10.95%) and (44.72 ± 15.64 pupae/ kg.f), respectively. Insecticides Success Appat® and Proteus 170 O-TEQ significantly reduced the damage of fruit flies in orchards.